STEAM power : infusing art into your STEM curriculum - Needles, Tim (International Society for Technology in Education, 2020)
This book offers ideas for blending arts and STEM learning (STEAM), focusing on creativity, innovation and collaboration. Includes fundamentals, project ideas and best practices, plus insight from educators, and covers coding, robotics, 3D printing, virtual/augmented reality, photography, video, animation and digital drawing. Offers ways to bring STEAM to the next level, such as collaboration, global learning, project-based learning, makerspaces and social-emotional learning.